Network analysis of somatic symptoms in Chinese patients with depressive disorder - Li, Yang; Jia, Shoumei; Cao, Baohua; Chen, Li; Shi, Zhongying; Zhang, Hao (Frontiers in Public Health, 2023)
Network theory conceptualizes somatic symptoms as a network of individual symptoms that are interconnected and influenced by each other. In this conceptualization, the network's central symptoms have the strongest effect on other symptoms. Clinical symptoms of patients with depressive disorders are largely determined by their sociocultural context. To our knowledge, no previous study has investigated the network structure of somatic symptoms among Chinese patients with depressive disorders. This study described this structure in patients with depressive disorders in Shanghai, China. In total, 177 participants were recruited between October 2018 and June 2019. The Chinese version of the Patient Health Questionnaire-15 was used to assess somatic symptoms. In order to quantify the somatic symptom network structure, indicators of “closeness,” “strength,” and “betweenness” were employed as identifiers for network-central symptoms. The symptoms of “feeling your heart pound or race,”“shortness of breath,” and “back pain” had the highest centrality values, indicating that these symptoms were central to the somatic symptom networks. Feeling tired or mentally ill had the strongest positive correlation with insomnia or other sleep problems (r = 0.419), followed by chest pain and breathlessness (r = 0.334), back pain, and limb or joint pain (r = 0.318). Psychological and neurobiological research that offers insights into somatic symptoms may focus on these central symptoms as targets for treatment and future research.